Experimental study on floatation of scheelite ore of Jiangxi - Wu, D.; Wen, S.; Yang, J.; Deng, J.; Liu, Jian (2014)
In this study, according to the characteristics of scheelite in run-of-mine, the scheelite was concentrated by adopting the full flotation process with sodium carbonate as regulator agent, sodium silicate as inhibitor for gangue minerals, lead nitrate as activator and ZL pharmacy as collector. 6.15% of the coarse scheelite concentration with tungsten recovery of 96.18% was obtained from the raw ores with grade of 0.86%. The concentration of rough tungsten by heating, by which the high-quality scheelite with tungsten of 62.31% and tungsten concentrate recovery of 93.53% was obtained.